Analisis Penerapan Teknik Penganggaran Investasi untuk Memperbaiki Kinerja Keuangan PT Fajar Riau Wisata - Risna, Rini (Politeknik Negeri Bengkalis, 2023)
This study aims to determine the application of investment budgeting techniques to improve the financial performance of PT. Fajar Riau Pekanbaru Tourism using capital budgeting techniques. This research uses a qualitative method with a descriptive analysis presentation. The data used in this study is quantitative data in the form of numerical data on the annual cash flow report for 2016â€“2020. The data used in this study are primary and secondary data obtained from direct interviews with the owner as Informant 1 and manager of PT. Fajar Riau Wisata Pekanbaru as Informant 2, and primary data in the form of company financial statements. This study uses several analytical methods, such as payback period (PP), net present value (NPV), and internal rate of return (IRR). The results of this study reveal that, based on the results of the calculation of the ARR value obtained of 50.90%, it can be concluded that the investment is feasible. The results of the calculation of the payback period for the additional units of bus vehicles that have been formulated are 6 years, 4 months, and 13 days. Based on the data, the NPV is greater than the planned investment value. The resulting NPV value is Rp 934,103,243. The investment plan is feasible because it produces a positive NPV value. Based on the resulting IRR value of 30.73%,. This value is greater than the capital issued by 12.58%, so the investment plan is feasible to implement.Â Keywords: Investment Budgeting Techniques, Financial Performance.